PENERAPAN HUKUM FARAIDH DALAM PEMBAGIAN HARTA WARIS DI KECAMATAN RANTO BAEK KABUPATEN MANDAILING NATAL SUMATERA UTARA - Hasan, Hasan (Jurnal Payung Sekaki : Kajian Keislaman, 2025)
The issue of inheritance or faraidh is always interesting to discuss. Although Indonesia is a country with a majority Muslim population, it does not mean that its people have implemented Islamic law, especially inheritance law, properly and correctly. According to the miraculous evidence of the Qur'an that explains the principle of the distribution of inheritance rights in farāidh, the distribution of inheritance rights in faraidh can provide justice and benefits for the beneficiaries. This concept is known as furudhul muqaddarah. This research utilizes qualitative research methods. By using a sampling model, this research studies the community of Ranto Baek Subdistrict, Mandailing Natal Regency. However, the subject of this research is the application of faraid law in land division in Ranto Baek Sub-district, Mandailing Natal Regency, North Sumatra. The study found that only some heirs have access to inherited property.